Local Involvement in Modern Greek Revivals of Ancient Theatres: Delphi and Epidaurus in the Interwar Period - Balaskas, Vasileios (Cambridge University Press, 2021)
Local community participation in the revival of ancient theatres as venues in Greece shaped the dynamics of the cultural reception of inter-war performances at Delphi and Epidaurus. Here I analyse local involvement within and beyond the theatrical context of the Delphic Festivals, as well as the long-standing identification of the village of Ligourio with the theatre of Epidaurus. These relationships reflect distinctive dimensions of the clash between community-led and institutional archaeology, which dominated national discourse on authenticity and identity. At the same time, the prospects of economic development through tourism in such remote areas encouraged local receptiveness to the revival of ancient theatres.
Keywords: Teatros - Conservación y restauración - Grecia; Local communities; Authenticity; National imagination; Greek National Theatre; Teatro Nacional de Grecia; Teatro de Epidauro